Improvement of the stand of automation of testing of functions of FPGA of components of hardware and software complexes of the Radics platform - Rudenko, A.; Golovko, A.; Ponochovniy, Y (Systems and Technologies, 2021)
The article shows the role of the testing and debugging stage in the life cycle of software products in assessing their reliability. Stages of testing of hardware and software complexes are allocated. The researches directed on optimization of a stage of testing and debugging of software products are analyzed; in which the characteristics of the method of accelerated testing of software reliability for graph-ical interfaces are considered and generalized; the division into stages of testing with comparison of results with model indicators is offered; the influence of test information on the assessment of software reliability is considered and the function of test coverage in the form of the generalized logistic function is offered. The char-acteristics of the factors, the consideration of which during testing increases the accuracy of assessing the reliability of software products, are considered. Features of modeling aimed at creating tools for testing software products are identified. Describes the architecture of the RadICS platform, which consists of a single in-strument chassis containing a logic module, as well as up to fourteen other input/ output and fiber-optic modules. Application Logic for the RadICS platform are de-veloped using a specialized Integrated Development Environment - Radiy Platform Configuration Tool. In this Integrated Development Environment, each Application Logic Block is represented graphically using visualization tools, which simplifies the management of functions (logical, mathematical, etc.). The Application Logic Block set in the Radiy Platform Configuration Tool creates a function block library (AFBL) and consists of more than one hundred block elements. An example of al-gorithm development for checking the quality and reliability of AFBL library block functions is demonstrated. The configuration of the test bench with manual testing is analyzed and its modification on the basis of the equipment and software of the National Instruments company is offered.